Exploring diversity rock-inhabiting fungi from northern Thailand: a new genus and three new species belonged to the family Herpotrichiellaceae - Thitla, Tanapol; Kumla, Jaturong; Hongsanan, Sinang; Senwanna, Chanokned; Khuna, Surapong; Lumyong, Saisamorn; Suwannarach, Nakarin (Frontiers in Cellular and Infection Microbiology, 2023)
Members of the family Herpotrichiellaceae are distributed worldwide and can be found in various habitats including on insects, plants, rocks, and in the soil. They are also known to be opportunistic human pathogens. In this study, 12 strains of rock-inhabiting fungi that belong to Herpotrichiellaceae were isolated from rock samples collected from forests located in Lamphun and Sukhothai provinces of northern Thailand during the period from 2021 to 2022. On the basis of the morphological characteristics, growth temperature, and multi-gene phylogenetic analyses of a combination of the internal transcribed spacer, the large subunit, and the small subunit of ribosomal RNA, beta tubulin and the translation elongation factor 1-a genes, the new genus, Petriomyces gen. nov., has been established to accommodate the single species, Pe. obovoidisporus sp. nov. In addition, three new species of Cladophialophora have also been introduced, namely, Cl. rupestricola, Cl. sribuabanensis, and Cl. thailandensis. Descriptions, illustrations, and a phylogenetic trees indicating the placement of these new taxa are provided. Here, we provide updates and discussions on the phylogenetic placement of other fungal genera within Herpotrichiellaceae.